2023
DOI: 10.31756/jrsmte.621
|View full text |Cite
|
Sign up to set email alerts
|

Have you heard about this? An exploration of instructor communication about campus resources to students in biology courses

Abstract: Campus resources provide valuable support for students navigating university, in particular historically excluded students. However, not all students may be aware of these resources or be actively encouraged to use them. As students regularly interface with their instructors for consecutive periods of time, instructor communication about campus resources regarding academic, community, wellness, and career and professional support may have positive motivational and psycho-social impacts for all students, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…During the time frame of the study, the campus was actively engaged in building a community of support for their students through the institution's mission and values, as well as concerted campaigns to promote community and belonging on campus. Vega and Meaders (2023) found that communication campaigns play an important role in student's information networks on campus. Students with lower feelings of belonging on campus and are less likely to seek out resources or spaces to belong on their own.…”
Section: Discussionmentioning
confidence: 99%
“…During the time frame of the study, the campus was actively engaged in building a community of support for their students through the institution's mission and values, as well as concerted campaigns to promote community and belonging on campus. Vega and Meaders (2023) found that communication campaigns play an important role in student's information networks on campus. Students with lower feelings of belonging on campus and are less likely to seek out resources or spaces to belong on their own.…”
Section: Discussionmentioning
confidence: 99%